Customer satisfaction on railway transport service in Malaysia (KTMB) - Mohammad Ismail, Isfanoorzaty Hayat; Zainuddin, Nizamuddin (2012)
This study is an overview of the perceptions of users of railway transport services in Malaysia.The survey also aims to obtain feedback on the perception of service user’s railway transportation and the satisfaction level of railway transport services in Malaysia.In addition, the survey was also made to identify the factors least demand for rail services in Malaysia.This study used statistical methods previous train service consumer perception, consumer demand data and other resources related to identifying the cause of the lack of demand for rail freight services.